Survival costs of reproduction are mediated by parasite infection in wild Soay sheep. (20th May 2019) - Leivesley, Jessica A.; Bussière, Luc F.; Pemberton, Josephine M.; Pilkington, Jill G.; Wilson, Kenneth; Hayward, Adam D.
Abstract: A trade‐off between current and future fitness potentially explains variation in life‐history strategies. A proposed mechanism behind this is parasite‐mediated reproductive costs: individuals that allocate more resources to reproduction have fewer to allocate to defence against parasites, reducing future fitness. We examined how reproduction influenced faecal egg counts (FEC) of strongyle nematodes using data collected between 1989 and 2008 from a wild population of Soay sheep in the St. Kilda archipelago, Scotland (741 individuals). Increased reproduction was associated with increased FEC during the lambing season: females that gave birth, and particularly those that weaned a lamb, had higher FEC than females that failed to reproduce. Structural equation modelling revealed future reproductive costs: a positive effect of reproduction on spring FEC and a negative effect on summer body weight were negatively associated with overwinter survival. Overall, we provide evidence that parasite resistance and body weight are important mediators of survival costs of reproduction.